Synthesis of copolymer thieno[3,4-b]thiophene and benzodithiophene for application in solar cells - C. Khantha (2018)
Synthesis of poly(2-hexylthieno[3,4-b]thiophene-co-4,8-didodecyloxybenzo[1, 2-b:4, 5-b-]dithiophene) (PTB) is presented using a simple and low cost method. Anhydrous DMF and toluene was added into the mixture of 4,6-dibromo-2- hexylthieno[3,4-b] thiophene,2,6-Bis(trimethyltin)-4,8-didodecyloxybenzo[1,2-b: 4,5-b-]dithiophene and Pd(PPh3)4. The polymerization was carried out at 120?C for 12 h. The PTB product was precipitated in methanol and dried in vacuum. The HOMO and LUMO energies of the polymer were calculated using Density Functional Theory (DFT) calculations to be compared with the experimental results. Copyright © Taylor & Francis Group, LLC.